Analysis of Public Interest Factors in the Jakarta Selata Region in the Use of Gopay as a Digital Payment - Martha Caesarilly; Hasnawati Zainal (Jurnal Indonesia Sosial Teknologi, 2024)
In this study, it is aimed at analyzing the interest of the community in the South Jakarta area in using GOPAY as a digital payment based on the Technology Acceptance Model (TAM). The Technology Acceptance Model (TAM) theoretical approach is used because it is the most widely used method in predicting information technology acceptance and has been proven to be a theoretical model that will be useful in helping to understand and explain user behavior and the implementation of the use of GOPAY as a digital payment. This is a consideration because people used to still use cash based payment instruments and now they have begun to recognize and use non-cash payment instruments in carrying out payment transaction activities. One of the non-cash payment instruments that is currently developing is electronic money, namely GOPAY. In this study, data was obtained using a questionnaire in the form of a google form and disseminated through the WhatsApp and other social media networks such as Instagram as many as 150 google forms have been filled. All answers are eligible for processing. The results of this study show that Perception of Benefits, Perception of Convenience, User Attitude, and Perception of Security partially have a positive effect on interest in using GOPAY as payment.